Platelet Aggregation after Exposure of Testosterone and Hight Glucose to Human Umbilical Vein Endothelial Cell Culture - Ikhlas Muhammad Jenie, Sri Kadarsih Soejono, Soejono Aswin, Budi Mulyono (Faculty of Geography Press, UGM, 2014)
Normal endothelial cells inhibits platelet activation, otherwise platelet plug and thrombus are subsequently be formed in blood vessels.